Mechanism of Antifungal Activity by 5-Aminoimidazole-4-Carbohydrazonamide Derivatives against Candida albicans and Candida krusei - Fátima Cerqueira; Marta Maia; Carla Gabriel; Rui Medeiros; Sara Cravo; Ana Isabel Ribeiro; Daniela Dantas; Alice Maria Dias; Lucília Saraiva; Liliana Raimundo; Eugénia Pinto (MDPI AG, 2021)
Systemic mycoses are one major cause of morbidity/mortality among immunocompromised/debilitated individuals. Studying the mechanism of action is a strategy to develop safer/potent antifungals, warning resistance emergence. The major goal of this study was to elucidate the mechanism of action of three (Z)-5-amino-N'-aryl-1-methyl-1H-imidazole-4-carbohydrazonamides (2h, 2k, 2l) that had previously demonstrated strong antifungal activity against Candida krusei and C. albicans ATCC strains. Activity was confirmed against clinical isolates, susceptible or resistant to fluconazole by broth microdilution assay. Ergosterol content (HPLC-DAD), mitochondrial dehydrogenase activity (MTT), reactive oxygen species (ROS) generation (flow cytometry), germ tube inhibition and drug interaction were evaluated. None of the compounds inhibited ergosterol synthesis. Ascorbic acid reduced the antifungal effect of compounds and significantly decreased ROS production. The metabolic viability of C. krusei was significantly reduced for values of 2MIC. Compounds 2h and 2k caused a significant increase in ROS production for MIC values while for 2l a significant increase was only observed for concentrations above MIC. ROS production seems to be involved in antifungal activity and the higher activity against C. krusei versus C. albicans may be related to their unequal sensitivity to different ROS. No synergism with fluconazole or amphotericin was observed, but the association of 2h with fluconazole might be valuable due to the significant inhibition of the dimorphic transition, a C. albicans virulence mechanism.